Respuesta :

Answer:

Roots are :  1, -7 and -7

Step-by-step explanation:

When we put x = -1 in F(x) it is equal to 0

Thus, (x + 1) is factor of given function.

When we divide F(x) by (x + 1) it gives the value (x² - 6x - 7)

factorizing the work  x² - 6x - 7 by middle term splitting.

> x² - 6x - 7 = x² - 7x + x - 7

>  x(x - 7) + 1(x - 7)

>  (x + 1) (x - 7)

then,  x³ - 5x² - 13x - 7 = (x + 1)(x + 1)(x - 7)

x = -1, -1, 7 the factor.

D and C is the answers.

Step-by-step explanation:

1 -7 7


Hope this helps you out